Old World and New World collision: Historic land grabs and the contemporary recovery of Indigenous land management practices in the western USA - Bulkan, J.; Palmer, J.; Larson, A.M.; Hobley, M. (Routledge, 2022)
This introduction to the chapters on community forestry in North America summarises the often-traumatic post-Columbian interactions between Native Americans and waves of immigrants mainly from Europe. The Indigenous land management, mostly by controlled ground fire set in small patches, enables annual harvests of multiple goods and services from the forest. This ‘light touch’ management is sensitive to local ecologies and reduces the risk of catastrophic fires, which have been exacerbated by a century of government attempts to stop all forest fires.